Research Trends of Piezoelectric Nanomaterials in Biomedical Engineering. Issue 1 (1st December 2022) - Ji, Jianying; Yang, Chunyu; Shan, Yizhu; Sun, Mingjun; Cui, Xi; Xu, Lingling; Liang, Shiyuan; Li, Tong; Fan, Yijie; Luo, Dan; Li, Zhou
Abstract : Piezoelectric nanomaterials are functional materials that hold a great promise for the nanoscale conversion of mechanical energy and electrical signals. Owing to their excellent electromechanical dependence, catalytic activity, and response sensitivity, piezoelectric nanomaterials are widely used in energy harvesting, sensors, actuators, resonators, and medical detectors. Nano‐piezoelectric materials exhibit unique electrical and chemical activities in the field of biomedical engineering, such as disease diagnosis and treatment. The working principles, device‐design mechanics, and classification of piezoelectric nanomaterials are systematically reviewed. Then, the recent advances in piezoelectric nanomaterials and their applications in tissue regeneration, antitumor/antibacterial therapy, cell force detection, controlled drug release, and pathological/physiological parameter monitoring are highlighted. Finally, the perspectives on the development of future smart piezoelectric nanomaterials, and how they can serve as a building block to inspire and impact the development of novel diagnosis and treatment applications, are presented. Abstract : Herein, the working principle, design, and classification of piezoelectric nanomaterials are systematically reviewed. The latest progress of piezoelectric nanomaterials and their applications in tissue regeneration, antitumor/antibacterial therapy, cell force detection, controlled drug release, and pathological/physiological parameter monitoring are highlighted. The summary of biomedical applications of piezoelectric nanomaterials will inspire novel diagnostic and therapeutic strategies in the future.